Highly efficient synthesis of γ-valerolactone by catalytic conversion of biomass-derived levulinate esters over support-free mesoporous Ni. (January 2021) - Chen, Han; Xu, Qiong; Zhang, Du; Liu, Wenzhu; Liu, Xianxiang; Yin, Dulin
Abstract: A series of mesoporous nickel catalysts with different molar ratios of citric acid and nickel nitrate were synthesized via a simple two-step method by solid-state grinding and in-situ reduction; these catalysts were further employed for the catalytic transfer hydrogenation of levulinate esters to γ-valerolactone (GVL) with 2-propanol as the hydrogen donor. The effects of C6 H8 O7 /Ni molar ratios, catalyst dosage, reaction temperature and time on the catalytic performance were investigated. An excellent GVL selectivity of 99.1% and an ethyl levulinate (EL) conversion of 100% could be achieved at 180 °C in 6 h over Ni-1.0 catalyst with a 1.0:1 M ratio of C6 H8 O7 /Ni. The characterization results showed that the Ni-1.0 catalyst was composed of mesoporous metallic Ni bulk and a surface Ni–NiO composite, and the acid sites of NiO played a synergistic catalytic role in producing GVL from EL. The superior mesoporous structure and large surface area of Ni-1.0 increased the atomic utilization rate of nickel metallic active centers. Moreover, Ni-1.0 catalyst could be easily separated and reused ten times, with an EL conversion above 95% remaining in each recycle. This work provids a highly efficient and environmentally friendly catalytic procedure for the conversion of biomass into GVL, a fuel additive compound. Graphical abstract: Image 1 Highlights: A simple and green method was used to prepare support-free mesoporous Ni catalysts. Ni catalysts were efficient for the transfer hydrogenation of levulinates to γ-valerolactone. An excellent γ-valerolactone yield of 99.1% was obtained over Ni-1.0 catalyst. Metallic Ni and co-existing surface NiO contribute to the high catalytic activity. Ni-1.0 catalyst preserved above 95% of conversion activity after ten consecutive cycles.